Marker detection and genetic analysis for rust resistance of recombinant and backcross inbred lines in groundnut (Arachis hypogaea L.) - Jakkeral, Shridevi A.; Nadaf, H. L.; Gowda, M. V. C.; Bhat, R.S.; Patil, R.K.; Motagi, Babu; Kenchanagowda, K.; Mukri, Ganapati; Archana, B.; Ganagshetty, Prakash; Gangadhar, K.; Jaggal, Lalitha (The Indian Journal of Genetics and Plant Breeding, 2017)
The present work was conducted to study the genetic variation and identification of microsatellite markers linked to rust resistance in groundnut. An F6mapping population and three backcross populations (BC1F4, BC2F3 and BC3F2) were developed from a cross between the susceptible parent GPBD-5 and resistant parent GPBD-4. There were highly significant differences among recombinants for reaction to rust. A little difference was observed between PCV and GCV for reaction to rust. High heritability coupled with high genetic advance as per cent of mean was observed for reaction to rust in F6, and backcross populations. Bulk segregant analysis in the segregating population of GPBD-5 x GPBD-4 indicated TC5A06 to be putatively linked to rust resistance i.e., single marker analysis (SMA). This marker can be used in marker assisted selection for rust resistance in groundnut improvement program.